2007
DOI: 10.1897/06-359r.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating mercury biomagnification in fish from a tropical marine environment using stable isotopes (δ13C AND δ15N)

Abstract: Concentrations of total mercury (T-Hg) and methylmercury (MeHg) were measured in zooplankton and 13 fish species from a coastal food web of the Gulf of Oman, an arm of the Arabian Sea between Oman and Iran. Stable isotope ratios (delta13C and delta15N) also were determined to track mercury biomagnification. The average concentration of T-Hg in zooplankton was 21 +/- 8.0 ng g(-1) with MeHg accounting 10% of T-Hg. Total mercury levels in fish species ranged from 3.0 ng g(-1) (Sardinella longiceps) to 760 ng g(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 38 publications
3
39
1
1
Order By: Relevance
“…The log Hg concentration-δ 15 N regression slope of 0.048 found in this study was comparable to the slope of 0.07 reported for Hg in a tropical coastal food web in the Gulf of Oman (Al-Reasi et al, 2007). However, this slope was remarkably smaller than that observed for the Mekong River food web (0.114) (Ikemoto et al, 2008), Arctic marine food webs (0.197-0.32) (Jarman et al, 1996;Atwell et al, 1998;Campbell et al, 2005) and for biota in Lake Murray, Papua New Guinea (0.28) (Bowles et al, 2001).…”
Section: Trophic Transfer Of Trace Elementssupporting
confidence: 88%
“…The log Hg concentration-δ 15 N regression slope of 0.048 found in this study was comparable to the slope of 0.07 reported for Hg in a tropical coastal food web in the Gulf of Oman (Al-Reasi et al, 2007). However, this slope was remarkably smaller than that observed for the Mekong River food web (0.114) (Ikemoto et al, 2008), Arctic marine food webs (0.197-0.32) (Jarman et al, 1996;Atwell et al, 1998;Campbell et al, 2005) and for biota in Lake Murray, Papua New Guinea (0.28) (Bowles et al, 2001).…”
Section: Trophic Transfer Of Trace Elementssupporting
confidence: 88%
“…Despite the importance of marine fish in human diets and high levels of Hg observed by monitoring agencies [2], much of the research that has been conducted on aquatic Hg cycling has occurred in freshwater ecosystems [3]. Studies of Hg bioaccumulation in marine ecosystems often examine fish collected from limited geographic areas [4][5][6][7]. How Hg concentrations in fish vary within ocean basins has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, differences in community productivity and structure are thought to influence the degree of biomagnification. Primary and secondary production, species diversity, food chain length and complexity (i.e., number of trophic links per species) are all believed to be influential factors affecting biomagnification efficiency (Cabana et al 1994;Stemberger and Chen 1998;Al-Reasi et al 2007). For example, Cabana et al (1994) found fish in lakes with longer food chains have higher Hg concentrations than fish from lakes with short food chains.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that structurally complex food webs, comprising many lateral links, may attenuate the degree of biomagnfication due to pathways that do not lead to top predators (Stemberger and Chen 1998). Other studies have subsequently argued that lower biomagnification in certain ecosystems may be attributed to more complex food webs (Al-Reasi et al 2007;Lavoie et al 2013).…”
Section: Introductionmentioning
confidence: 99%